Racismo científico: o eu, o outro e o nós: práticas para o ensino de biologia - Pitanga, Letícia Pitelli (Universidade Federal de São Carlos, 2022)
This Academic Work aims to propose, from the theme of Scientific Racism, the elaboration and analysis of a didactic sequence that can address racism and science as points to understand promote the teaching for Ethnic-Racial Relationships, in line with the brasilian law 10.639/2003, possibilite understand historically what are the social implications, that this violence has created and how we can overcome it through genetics, content addressed in biology education for the 2nd year of high school. As a way of structuring the didactic sequence, we will use the methodological proposal of “The Three Pedagogical Moments” considering Dialogical Learning that from it is principles, promotes learning through dialogue and social transformation, together withSuccessful Educational Actions, specifically Dialogical Reading and Interactive Groups as part of the activities proposed below.
Scientifc racism: I, another and us: practices for biology teaching
Keywords: Racismo científico; Ensino de biologia; Aprendizagem dialógica; Genética; Scientific racism; Biology teaching; Dialogical learning; Genetics; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO